Prognosis of patients with prostate cancer and bone metastasis from the Japanese Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index cohort study. (19th June 2021) - Nakajima, Kenichi; Mizokami, Atsushi; Matsuyama, Hideyasu; Ichikawa, Tomohiko; Kaneko, Go; Takahashi, Satoru; Shiina, Hiroaki; Horikoshi, Hiroyuki; Hashine, Katsuyoshi; Sugiyama, Yutaka; Miyao, Takeshi; Kamiyama, Manabu; et al.
Abstract : Objective: To determine prognostic factors including the Bone Scan Index in prostate cancer patients receiving standard hormonal therapy and chemotherapy. Methods: This multicenter Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index study involved 30 hospitals and enrolled 247 patients (age 71 ± 8 years) with metastatic hormone‐sensitive prostate cancer ( n = 148) under hormone therapy and metastatic castration‐resistant prostate cancer ( n = 99) under chemotherapy. The Bone Scan Index (%) was determined by whole‐body bone scintigraphy using 99m Tc‐methylenediphosphonate. Patients were classified into tertiles and binary groups, and predictors of all‐cause death including Bone Scan Index, prostate‐specific antigen, and bone metabolic markers were determined using survival and proportional hazard analyses. Results: During a mean follow‐up period of 716 ± 404 days, 81 (33%) of the patients died, and 3‐year mortality rates were 20% and 52% in the metastatic hormone‐sensitive prostate cancer and metastatic castration‐resistant prostate cancer groups, respectively. Survival analysis showed that a Bone Scan Index >3.5% was a significant determinant of death in the metastatic hormone‐sensitive prostate cancer group, whereas prostate‐specific antigen >55 ng/mL before chemotherapy was a determinant of prognosis in the metastatic castration‐resistant prostate cancer group. A Bone Scan Index >3.5% was also associated with a high incidence of prostate‐specific antigen progression in the metastatic hormone‐sensitive prostate cancer group. Patients with metastatic hormone‐sensitive prostate cancer and a better Bone Scan Index response (>45%) to treatment had lower mortality rates than those without such response. Conclusion: The Bone Scan Index and hot spot number are significant determinants of 3‐year mortality, and combining the Bone Scan Index with prostate‐specific antigen should contribute to the management of prostate cancer patients with bone metastasis.